A Model of Socio-Ecological and Economic System: The Tula Region of the Russian Federation - ZHUKOV, Roman Aleksandrovich; KUZNETSOV, Gennadiy Vasilievich; FOMICHEVA, Irina Viacheslavovna; MYASNIKOVA, Elena Borisovna; VASINA, Marina Vladimirovna; TSIGLER, Maksim Vladimirovich (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
This paper aims to present the model of socio-ecological and economic system for the Tula region of the Russian Federation and to make calculations related to the assessment of their state and functioning. The model is compared with the model constructed for the regions of the Central Federal district. We apply the author's methodological toolkit that includes the formation of individual and integrated indicators of the functioning of complex systems, considered as socio-ecological and economic systems. The paper results are as follows: the model is presented with 9 generalized performance indicators, 26 individual performance indicators, 47 factor indicators (state and impact factors) and 4 latent variables using open data from the Federal State Statistics Service of the Russian Federation for 2004-2016. Included is also the analysis of the results.